2023
DOI: 10.7324/japs.2023.117478
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-glucosidase inhibitory activity of the combination of Caesalpinia sappan L. and Garcinia mangostana extract

Abstract: Garcinia mangostana (Gm) and Caesalpinia sappan (Cs) are traditional food used for health supplements. Nevertheless, the synergistic effect of the combinations has never been studied for antidiabetic supplements. This study aimed to evaluate the synergistic α-glucosidase activity of Gm pericarp and Cs heartwood combination extracts. Both plants were extracted with ethanol and water. The total flavonoid content was measured by colorimetric assay. The α-glucosidase inhibitory assay was used to measure the α-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For example, Faisal Usman et al [ 54 ], Qirou Wang et al [ 55 ], and Juan Cardozo-Muñoz et al [ 56 ] conducted computational experiments without a positive control, resulting in insufficient evidence to support the reliability of their docking results for α-mangostin and α -glucosidase. On the other hand, Nina Artanti et al [ 57 ] and Ahmad Fariz Maulana et al [ 58 ] used acarbose as a positive control, but their docking results did not accurately reflect the in vitro experimental results. In this study, α-mangostin was demonstrated to be a potent α -glucosidase inhibitor, with an IC 50 value of 1.90 ± 0.10 μg/mL (equivalent to 4.63 ± 0.24 μM), whereas the IC 50 value of acarbose was 134.56 ± 3.02 μg/mL (equivalent to 204.93 ± 4.60 μM).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Faisal Usman et al [ 54 ], Qirou Wang et al [ 55 ], and Juan Cardozo-Muñoz et al [ 56 ] conducted computational experiments without a positive control, resulting in insufficient evidence to support the reliability of their docking results for α-mangostin and α -glucosidase. On the other hand, Nina Artanti et al [ 57 ] and Ahmad Fariz Maulana et al [ 58 ] used acarbose as a positive control, but their docking results did not accurately reflect the in vitro experimental results. In this study, α-mangostin was demonstrated to be a potent α -glucosidase inhibitor, with an IC 50 value of 1.90 ± 0.10 μg/mL (equivalent to 4.63 ± 0.24 μM), whereas the IC 50 value of acarbose was 134.56 ± 3.02 μg/mL (equivalent to 204.93 ± 4.60 μM).…”
Section: Resultsmentioning
confidence: 99%
“…The number of hydrogen bonds and non-covalent interactions for each complex was calculated using Discovery Studio Visualizer (http://accelrys.com/products/collaborative-science/biovia-discovery-studio/, accessed on 16 November 2023), which produced details, compound images, and interaction images (2D and 3D). We used web-based pkCSM-pharmacokinetic tools to determine the pharmacokinetics (absorption, distribution, metabolism, and excretion); safety; and physicochemical properties of the selected bioactive molecules [43,47].…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%